Environmental assessment of construction and demolition waste recycling in Bolivia: Focus on transportation distances and selective collection rates. Issue 6 (June 2022) - Ferronato, Navarro; Guisbert Lizarazu, Gabriela Edith; Gorritty Portillo, Marcelo Antonio; Moresco, Luca; Conti, Fabio; Torretta, Vincenzo
Construction and demolition waste (CDW) management in developing countries is a global concern. The analysis of scenarios and the implementation of life cycle assessment (LCA) support decision-makers in introducing integrated CDW management systems. This paper introduces the application of an LCA in La Paz (Bolivia), where CDW is mainly dumped in open areas. The aim of the research is to evaluate the benefits of inert CDW recycling in function of the selective collection rate, defined as the amount of waste (%wt. ) sorted at the source in relation to the total waste amount produced, and the distances from the CDW generation to the material recycling facility. The outcomes of the research suggest that increasing the selective collection rates (5% to 99%) spread the importance of transportation distances planning since it affects the magnitude of the environmental impacts (1.05 tCO2 -eq to 20.7 tCO2 -eq per km traveled). Transportation limits have been found to be lower than about 40 km in order to make recycling beneficial for all environmental impacts and for all selective collection rate, with the eutrophication potential as the limiting indicator. The theoretical analysis suggests implementing LCA with primary data and involving statistics related to the transportation of virgin materials avoided thanks to recycling. The outcomes of the research support the implementation of CDW recycling in developing countries since it has been found that material recovery is always beneficial.